Do You Get me? Strategies to Create Learning in Tennis10s! - Barrell, Mike (ITF Coaching & Sport Science Review, 2013)
This article will discuss in detail ways in which learning can be more efficient and improved in Tennis10s. Different types of learning will be highlighted, such as implicit and stimulating, and evaluated as methods for improving the learning of Under 10 children. Useful tips and advice will be given to the reader in order to promote a better learning environment.